Origin of eukaryotic plasmalogen biosynthesis by horizontal gene transfer from myxobacteria - Juan Manuel Trinidad-Barnech; Irene del Rey Navalón; Konstantina Mitsi; Antonio J. Monera-Girona; Sebastian R. Najle; S. Padmanabhan; Iñaki Ruiz-Trillo; Montserrat Elías-Arnanz (Proceedings of the National Academy of Sciences, 2026)
Plasmalogens are a unique class of glycerophospholipids defined by a distinctive vinyl ether bond. While these lipids are abundant in animals and important for human health, their evolutionary history remains enigmatic, mostly due to their absence in some major eukaryotic lineages like plants. Here, we resolve the origin and evolution of the aerobic plasmalogen biosynthesis pathway in eukaryotes. Through comprehensive phylogenomic analysis and experimental validation of enzyme activity and plasmalogen presence, we demonstrate that the essential desaturase plasmanylethanolamine desaturase 1 (PEDS1)—and likely the fatty acyl-CoA reductase (FAR) and glycerone phosphate O -acyltransferase (GNPAT) enzymes also critical in the pathway—were acquired by an early eukaryotic ancestor through horizontal gene transfer (HGT) from myxobacteria. Our data show that this bacterial pathway was retained in the Amorphea and Discoba supergroups but lost or replaced in others. The findings yield insights into how HGT shaped metabolic pathways in early eukaryotes.